Comparative study of clinical and metabolic characteristics of polycystic ovary syndrome (PCOS) among Sri Lankan women from a tertiary clinic versus. a community setting - Kumarapeli, V.; Jayarathna, R.N.; Wijeyaratne, C.N. (My University, 2007)
The manifestations of PCOS are linked to insulin resistance and hyperandrogenism OBJECTIVE To compare clinical and metabolic characteristics of Sri Lankan women with PCOS managed in a clinic versus, those detected by a community survey METHODS Data of a cohort of newly diagnosed women with PCOS diagnosed by a community survey in Gampaha (2005) with 198 consecutive women with well characterised PCOS attending a tertiary endocrine clinic in Colombo (2002 to 2005). RESULTS Clinic based women vs. community sample : median FG score was significantly higher 10.6 vs 4.74 (p < 0.05); those with BMI >25 kg/m2 was 61.8 percent vs 43.5 percent was significantly greater (p<0.01). Mean fasting plasma insulin (_g/dl) was 27.15 vs, 7.2, total cholesterol (mg/dl) 200.9 vs. 181.46, triglycerides (mg/dl) 119.34 vs 106.12, and LDL (mg/dl) 133.29 vs 114.27 were significantly higher among clinic based women. Prevalence of hypertension 26.1 percent vs 10.9 percent was also significantly higher (p<0.05) greater among the clinic attendees although diabetes mellitus was 6.7 percent vs 3.4 percent and not significant. CONCLUSIONS AND RECOMMENDATIONS This data confirms that women with PCOS who are referred to specialist clinics have a far greater degree of metabolic derangement that those who were identified by community based screening.
Keywords: pcos; tertiary care; Sri Lankan